Pengaruh Kecepatan Pengaduk Ganda dan Waktu Pengadukan pada Mesin Pencampur terhadap Homogenitas Sampah Organik dalam Proses Pengomposan - Raka Galang Rustio Wardoyo; Haris Puspito Buwono (Jurnal Teknik Mesin, Industri, Elektro dan Informatika, 2025)
Waste is an unavoidable problem along with increasing population activity due to population growth, which causes the amount of waste to increase, especially from traditional markets, tourist areas, dense settlements, and public facilities. In Malang City, waste in 2023 is estimated to reach 778.34 tons, so proper and environmentally friendly management is needed, one of which is by processing organic waste into a homogeneous compost mixture using a mixing machine. This study aims to analyze the effect of double mixer speed and mixer time on the mixing machine on the homogeneity of organic waste in the composting process. The research method used is quantitative experimental with factorial experimental design (DOE) for the effect of double mixer speed and mixer time on the homogeneity of organic waste in the composting process. The double mixer speed variations tested were 20, 45, and 60 RPM, with mixing times of 20, 30, and 40 minutes. The results showed that the double mixer speed and stirring time had a significant effect on the homogeneity of organic waste in the composting process, with an optimal increase in homogeneity occurring at a speed of 60 RPM and a duration of 40 minutes. Higher speeds accelerate particle distribution, while sufficient mixing time ensures even distribution, thereby increasing the efficiency of microbial decomposition.